Targeting heparan sulfate proteoglycans as an effective strategy for inhibiting cancer cell migration and invasiveness compared to heparin - Depau, Lorenzo; Brunetti, Jlenia; Falciani, Chiara; Mandarini, Elisabetta; Zanchi, Marta; Paolocci, Maria Francesca; Garfì, Marta; Pini, Alessandro; Bracci, Luisa (Frontiers in Cell and Developmental Biology, 2025)
By virtue of their ability to bind different growth factors, morphogens and extracellular matrix proteins, heparan sulfate proteoglycans (HSPGs) play a determinant role in cancer cell differentiation and migration. Despite a strong conceptual basis and promising preclinical results, clinical trials have failed to demonstrate any significant advantage of administering heparin to oncology patients. We exploited our anti-heparan sulfate branched peptide NT4 to test the opposite approach, namely, targeting HSPGs to interfere with their functions, instead of using heparin as a soluble competitor in human cell lines from pancreas adenocarcinoma, colon adenocarcinoma, rhabdomyosarcoma and two different breast cancers. We found that the anti-heparan sulfate peptide NT4 is more effective than heparin for inhibiting cancer cell adhesion, directional migration, colony formation and even cell growth, suggesting that targeting cell membrane HSPGs may be a more effective anti-metastatic strategy than using soluble heparin. Analysis of NT4 effects on cancer cell directional migration, associated to cellular distribution of HSPGs and cadherins in different migrating cancer cell lines, provided further indications on the molecular basis of HSPG functions, which may explain the efficiency of the HSPG targeting peptide.